2015
DOI: 10.1378/chest.14-0672
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Airflow Obstruction Among Veterans with Presumed Empirical Diagnosis and Treatment of COPD

Abstract: BACKGROUND: Despite guideline recommendations, patients suspected of having COPD oft en are treated empirically instead of undergoing spirometry to confi rm airfl ow obstruction (AFO). Accurate diagnosis and treatment are essential to provide high-quality, value-oriented care. We sought to identify predictors associated with AFO among patients with and treated for COPD prior to performance of confi rmatory spirometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 36 publications
4
37
2
Order By: Relevance
“…While we did not specifically examine allergic rhinitis, we did not find a higher risk of asthma (another allergic condition) among this group. Our results are also not consistent with a study that found increased body mass index (BMI) to be associated with higher risk of overdiagnosis in veterans [13]. These inconsistencies could be due to differences in populations, the exclusion of nonsmokers and people with asthma in the other studies, how BMI was considered (as a continuous versus categorical variable) and variability in other factors adjusted for.…”
contrasting
confidence: 99%
“…While we did not specifically examine allergic rhinitis, we did not find a higher risk of asthma (another allergic condition) among this group. Our results are also not consistent with a study that found increased body mass index (BMI) to be associated with higher risk of overdiagnosis in veterans [13]. These inconsistencies could be due to differences in populations, the exclusion of nonsmokers and people with asthma in the other studies, how BMI was considered (as a continuous versus categorical variable) and variability in other factors adjusted for.…”
contrasting
confidence: 99%
“…8,18 All patients aged 43 and older with physiciandiagnosed COPD between 2005 and 2012 were identified using a previously validated case-definition of physician-diagnosed COPD: age 35 years and older, and 1 or more COPD-related hospital admission or 3 or more physician COPD ambulatory care visits within 2 years. 19,20 This case definition has a specificity of 95% and a positive predictive value of 81% compared with a clinical reference standard (which may or may not have considered pulmonary function testing).…”
Section: Study Populationmentioning
confidence: 99%
“…Diagnosing COPD in patients with HF is essential both because dyspnoea in patients with both diseases presents a particular challenge and because the combination of COPD and HF identifies a high-risk population [14]. Furthermore can a normal spirometric examination rule-out the coexistence of COPD and other lung disease which might avoid the use of unnecessary medication and help the clinician in focusing on the heart disease [5]. Studies of patients with HF have shown a prevalence of self-reported COPD of 10–33% [1, 3, 6] and studies of spirometry in patients with HF have shown an even higher prevalence of COPD (30–39%).…”
Section: Introductionmentioning
confidence: 99%